Biofloc Microbiome With Bioremediation and Health Benefits - Kumar, Vikash; Roy, Suvra; Behera, Bijay Kumar; Swain, Himanshu Sekhar; Das, Basanta Kumar (Frontiers in Microbiology, 2021)
The biofloc system has recently attracted great attention as a cost-effective, sustainable, and environmentally friendly technology and expected to contribute toward human food security (Zero Hunger SDG 2). It is also expected that this endeavor can be adopted widely because of its characteristics of zero water exchange and reduced artificial feeding features. In the biofloc system, the flocs which are generally formed by aggregation of heterotrophic microorganisms, serve as natural bioremediation candidates. These microbes effectively maintain water quality by utilizing the nutrient wastes, mostly originated from digested, unconsumed, and metabolic processes of feed. Additionally, the flocs are important sources of nutrients, mainly a protein source, and when these are consumed by aquaculture animals they improve the growth performance, immunity, and disease tolerance of host against pathogenic microbial infection. Here in this review, we focus on recent advances that could provide a mechanistic insight on how the microbial community developed in the biofloc system helps in the bioremediation process and enhances the overall health of the host. We have also tried to address the possible role of these microbial communities against growth and virulence of pathogenic microbes.